2014
DOI: 10.1073/pnas.1319268111
|View full text |Cite
|
Sign up to set email alerts
|

Nonagonistic Dectin-1 ligand transforms CpG into a multitask nanoparticulate TLR9 agonist

Abstract: CpG DNA, a ligand for Toll-like receptor 9 (TLR9), has been one of the most promising immunotherapeutic agents. Although there are several types of potent humanized CpG oligodeoxynucleotide (ODN), developing "all-in-one" CpG ODNs activating both B cells and plasmacytoid dendritic cells forming a stable nanoparticle without aggregation has not been successful. In this study, we generated a novel nanoparticulate K CpG ODN (K3) wrapped by the nonagonistic Dectin-1 ligand schizophyllan (SPG), K3-SPG. In sharp cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
109
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 37 publications
7
109
0
Order By: Relevance
“…When the distribution patterns of HP-b-CD and OVA were compared using Volocity's colocalization analysis, injected OVA was distributed more selectively in MARCO + macrophages than was HP-b-CD (Pearson correlation: HP-b-CD, +0.548, OVA, +0.756) (Fig. 2A, Supplemental Video 1), which is consistent with our recent observation (24). The recent study indicated that, although OVA and CpG (K3-SPG) were incorporated primarily into MARCO + macrophages, the macrophages are dispensable for inducing adaptive immune responses by CpG (K3-SPG).…”
Section: Distribution Of Hp-b-cd and Ova In Draining Lnssupporting
confidence: 91%
“…When the distribution patterns of HP-b-CD and OVA were compared using Volocity's colocalization analysis, injected OVA was distributed more selectively in MARCO + macrophages than was HP-b-CD (Pearson correlation: HP-b-CD, +0.548, OVA, +0.756) (Fig. 2A, Supplemental Video 1), which is consistent with our recent observation (24). The recent study indicated that, although OVA and CpG (K3-SPG) were incorporated primarily into MARCO + macrophages, the macrophages are dispensable for inducing adaptive immune responses by CpG (K3-SPG).…”
Section: Distribution Of Hp-b-cd and Ova In Draining Lnssupporting
confidence: 91%
“…82 The triple-helical complex (K3-SPG) composed of a one-molecule CpG ODN and a two-molecule single-stranded SPG, linking 40 nt of phosphorothioated poly-A to the 3′ end of K3, known as CpG-B ODN, formed rod-like nanoparticles with a free rotation diameter of ~30 nm. 83 These self-assembled K3-SPG nanoparticles induced the secretion of IFN-α and IFN-γ from PBMCs. Additionally, when K3-SPG was administered to mice at the same time as OVA, there was increased production of OVA-specific IgG2c antibodies and induction of OVAspecific CTLs.…”
mentioning
confidence: 99%
“…[22][23][24] It has been reported that complexation of conventional CpG-B (ss CpG-B-PT) with materials such as cationic peptides, polycations, and polysaccharides confers conventional CpG-B with the capacity to induce type-I IFN. [28][29][30][31][32] In this study, we demonstrate that in a complex with Lipo, ds CpG-B72-PD designed based on the ss CpG-B24-PT sequence (known as the conventional CpG-B ODN2006) is a potent inducer of IFN-β as compared to ss CpG-B24-PT. ds CpG-B72-PD is a proinflammatory inducer that is similar to conventional CpG-B but has a ds native PD backbone instead of an ss artificial PT backbone.…”
Section: Discussionmentioning
confidence: 75%
“…However, these CpG ODNs form uncontrollable higher-order structures due to their palindromic and/or poly-G sequences, 21,25,26 which precludes their clinical application. 27 One way to overcome this problem is complexation of CpG-B with other materials such as cationic peptides, polycations, and polysaccharides, [28][29][30][31][32] because multimerization of conventional CpG-B converts it from an inducer of proinflammatory cytokines to one of type-I IFN. However, complexation can be costly and complicated; this limits the use of CpG-B complexes as an adjuvant for vaccines with high coverage such as influenza vaccine.…”
mentioning
confidence: 99%